(untitled) (Journal of the Bangladesh Agricultural University, 2026)
This study explored the impact of different feeding systems on dairy cattle performance in Mymensingh Sadar Upazila, Bangladesh, focusing on milk production, reproduction, and overall output. Three groups were examined: Intensive Holstein Friesian (HF) crossbreds, Semi-intensive HF crossbreds, and Semi-intensive Local cattle. The study found significant differences in feeding methods across the groups. Intensive HF crossbreds were stall-fed with German grass and concentrates, while Semi-intensive HF and Local cattle had access to both stall food and grass. Local cows primarily relied on rice straw. On average, each animal consumed 25.96 kg of feed daily, with Intensive HF crossbreds consumed the greatest amount of feed (20.59 kg). Milk production varied significantly, with Intensive HF crossbreds yielding 6.63 L/day, Semi-intensive HF at 3.99 L/day, and Local cattle at 1.98 L/day. Intensive HF cows also had the highest lactation yield of 1655.45 L. Reproductive traits showed that Intensive HF cows matured earlier (15.15 months) and had shorter calving intervals (13.1 months), indicating better performance in well-managed systems. Milk composition analysis revealed that Local cows produced milk with higher fat content, while Intensive HF cows had higher protein and lactose levels, enhancing milk quality. However, Intensive systems require higher inputs in terms of feed, labor, and veterinary care, making them costly. Semi-intensive HF systems offer a more balanced, cost-effective option, while Local cattle are suited for low-input systems with higher milk fat content, valuable in local markets. J Bangladesh Agril Univ 24(2): 64–72, 2026